Highlander unmasked : a novel - McCarty, Monica (MacLeods of Skye trilogy., 2007)
Meg Mackinnon, desperate to find a trustworthy husband to support her simple brother as Chief, meets Alex MacLeod, a mercenary outlaw who hides his mission to protect the Highlands and its people from the king's injustice.